Morphological and thermal stability characteristics of oil palm frond and trunk by ultrasound-low alkali-based pretreatment - Madusari, Sylvia; Bindar, Yazid; Prakoso, Tirto; Noor Ida Amalina, Ahamad Nordin; Saidatul Shima, Jamari (Elsevier Ltd, 2023)
Oil palm fronds and trunks leave a lot of lignocellulosic residues in the agricultural field. Due to its highly complex chemical composition, the lignocellulosic matrix is difficult to break down. This study aims to investigate the effects of chemo-physical pretreatment of oil palm fronds and trunks with ultrasound in a low alkali concentration solution. The microstructure and thermal stability of the oil palm frond and trunk were investigated using scanning electron microscopy (SEM) and a thermogravimetric (TG) method. SEM analysis proved the deterioration of the lignocellulose matrix of the ultrasound-assisted alkali pretreatment compared to raw. According to the TG results, the decomposition temperature curve of treated oil palm shifted to the right side after 50 percent mass degradation, indicating more excellent thermal stability than untreated oil palm biomass. On the other hand, at a temperature above 350 °C, the pretreated biomass has less thermal stability. It has been demonstrated that a combination of low chemical concentration and physical pretreatments can disrupt the oil palm lignocellulose microstructure and potentially shorten the time required to achieve maximum hydrolysis efficiency. Furthermore, ultrasonication power of 300 W, frequency of 40 kHz, temperature of 80 °C, and time of 30 min in combination with low alkali-based pretreatment in oil palm residue will be helpful in applications requiring greater thermal stability.